Immune response of heterologous versus homologous prime-boost regimens with adenoviral vectored and mRNA COVID-19 vaccines in immunocompromised patients - Chu, Chang; Schönbrunn, Anne; Fischer, Dorothea; Liu, Yvonne; Hocher, Johann-Georg; Weinerth, Jutta; Klemm, Kristin; Baehr, Volker von; Krämer, Bernhard; Elitok, Saban; Hocher, Berthold (Frontiers in immunology, 2023)
Due to rare but major adverse reactions to the AstraZeneca adenoviral ChAdOx1-S-nCoV-19 vaccine (ChAd), German health authorities recommended adults under 60 who received one dose of ChAd, to receive a second dose of the BioNTech mRNA BNT162b2 vaccine (BNT) as a booster. Studies in the general population suggest an enhanced efficacy of the heterologous (ChAd-BNT) compared to the homologous (BNT-BNT) vaccination regimen. However, an analysis of the efficacy in patient populations with a high risk of severe COVID-19 due to acquired immunodeficiency is still missing. We therefore compared both vaccination regimens in healthy controls, patients with gynecological tumors after chemotherapy, patients on dialysis and patients with rheumatic diseases concerning the humoral and cellular immune response. The humoral and cellular immune response differed substantially in healthy controls compared to patients with acquired immunodeficiency. Overall, the most significant differences between the two immunization regimens were found in neutralizing antibodies. These were always higher after a heterologous immunization. Healthy controls responded well to both vaccination regimens. However, the formation of neutralizing antibodies was more pronounced after a heterologous immunization. Dialysis patients, on the other hand, only developed an adequate humoral and particularly cellular immune response after a heterologous immunization. Tumor and rheumatic patients also - to a weaker extent compared to dialysis patients - benefited from a heterologous immunization. In conclusion, the heterologous COVID-19 vaccination regimens (ChAd-BNT) seem to have an advantage over the homologous vaccination regimens, especially in immunocompromised patients such as patients with end-stage kidney disease treated with hemodialysis.
Gesehen am 12.07.2023